Association Between Fear and Beauty Evaluation of Snakes: Cross-Cultural Findings - Landová, Eva; Bakhshaliyeva, Natavan; Janovcová, Markéta; Peléšková, Šárka; Suleymanova, Mesma; Polák, Jakub; Guliev, Akif; Frynta, Daniel (Frontiers in Psychology, 2018)
According to the fear module theory, humans are evolutionarily predisposed to perceive snakes as prioritized stimuli and exhibit a fast emotional and behavioral response towards them. In Europe, highly dangerous snake species are distributed almost exclusively in the Mediterranean and Caspian areas. While the risk of a snakebite is relatively low in Central Europe, Azerbaijan, on the other hand, has a high occurrence of the deadly venomous Levant viper (Macrovipera lebetina). We hypothesize that co-habitation with this dangerous snake has shaped the way in which humans evaluate snake species resembling it. For that purpose, we asked respondents from the Czech Republic and Azerbaijan to rank photographs depicting 36 snake species according to perceived fear and beauty. The results revealed a high cross-cultural agreement in both evaluations (fear r2 = 0.683, p < 0.0001; beauty: r2 = 0.816, p < 0.0001). Snakes species eliciting higher fear tend to be also perceived as more beautiful, yet people are able to clearly distinguish between these two dimensions. Deadly venomous snakes representing a serious risk are perceived as highly fearful. This is especially true for the vipers and allies (pit vipers) possessing a characteristic body shape with a distinct triangular head and thick body, which was found as the most fear evoking by respondents from both countries. Although the attitude toward snakes is more negative among the respondents from Azerbaijan, their fear evaluation is similar to the Czechs. For instance, despite co-habitation with the Levant viper, it was not rated by the Azerbaijanis as more fearful than other dangerous snakes. In conclusion, agreement in the evaluation of snake fear and beauty is cross-culturally high and relative fear attributed to selected snake species is not directly explainable by the current environmental and cultural differences. This may provide some support for the evolutionary hypothesis of preparedness to fear snakes.